The Role of Digital Advertising in the 2024 Indonesian Presidential Election - Muhammad Maulana; Inas Hamdan Billah; Muhammad Fathier Alkahfie; Akhirul Aminulloh (Universitas Negeri Malang, 2024)
Advertising is one of the strategies widely used by companies in promoting their products or services to the public. The functions of advertising are to provide information that makes consumers aware of a brand, persuade consumers to try the advertised product or service, maintain consumer memory of the advertised product or service, as an added value to the advertised product, and as a companion to efforts made by the company in terms of promotion. In the rapid development of technology, this also affects the advertising strategies carried out, one of which is by using mass media, such as television, radio, magazines and newspapers. Mass media itself comes from the word media, which is a tool or means used to convey from communicators to audiences while